If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3d-(d+4=-2
We move all terms to the left:
3d-(d+4-(-2)=0
We calculate terms in parentheses: -(d+4-(-2), so:We add all the numbers together, and all the variables
d+4-(-2
We add all the numbers together, and all the variables
d
Back to the equation:
-(d)
2d=0
d=0/2
d=0
| 1=v+14/10 | | m+31=9 | | -3(4t-4)+9t=5t-5 | | 14b-2=9 | | x-1/5x=84 | | 5(x+1)^2)=90 | | 3(2n+2)=8(6n+1)+4 | | 14w=-56 | | 48-(-42x-30)=252x+228 | | 7(2+2x)+(x+2)*6=0 | | X+10y=307 | | 6-4/4-x=3/5 | | 1/5(-20k+75)=5+10k | | 17z+33=6z | | 4g+(6+2g)*3=0 | | 3x-7=4-2(3x-4) | | (2)/(x)+3=(4)/(5x)+(31)/(10) | | 1/5+1/4+v=7/60 | | 2×+y=60 | | (3n+6)*3+(2n+2)*4=0 | | 0.2(x-20)=4 | | 3a=5a-20 | | 48-(-63x-30)=252x+228 | | -(3x-5)+x=-5x+1+x | | x^2-7x+11=5 | | X/3-x/4=7/2 | | 6n-12=-8+3n-8 | | 1+8b=-15+6b | | 6n-12=3n-16 | | 15x-13+7x+19=180 | | 15=6-2x | | 4(x+1)-2x=5x-8 |